2020
DOI: 10.1007/s00603-020-02300-2
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Initiation, Gas Ejection, and Strain Waves Measured on Specimen Surfaces in Model Rock Blasting

Abstract: Crack velocity, gas ejection, and stress waves play an important role in determining delay time, designing a blast and understanding the mechanism of rock fragmentation by blasting. In this paper, the emerging times of the earliest cracks and gas ejection on the lateral surfaces of cylindrical granite specimens with a diameter of 240 mm and a length of 300 mm were determined by high-speed photography, and the strain waves measured by an instrument of dynamic strain measurement during model blasting. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In addition, Fourney (2015) showed that the S-wave induced by the reflection of the compressive wave at the free surface might cause cracks in the radial direction of a blast model. Interestingly, in model blasting (Chi et al 2019a;Zhang et al 2021a), some radial cracks were discovered on the free surfaces of the rock specimens, but no gas was ejected out of such radial cracks, meaning that these radial cracks were initiated from the free surfaces rather than from the blastholes. This is consistent with the analysis by Fourney (2015) to a certain extent.…”
Section: Free Surface and Barrier Nearbymentioning
confidence: 99%
“…In addition, Fourney (2015) showed that the S-wave induced by the reflection of the compressive wave at the free surface might cause cracks in the radial direction of a blast model. Interestingly, in model blasting (Chi et al 2019a;Zhang et al 2021a), some radial cracks were discovered on the free surfaces of the rock specimens, but no gas was ejected out of such radial cracks, meaning that these radial cracks were initiated from the free surfaces rather than from the blastholes. This is consistent with the analysis by Fourney (2015) to a certain extent.…”
Section: Free Surface and Barrier Nearbymentioning
confidence: 99%
“…Fractured zone was contribute to main part of rock fragmentation by blasting in engineering, the failure range of which was much larger than that of crushed zone. The length, velocity of crack and damage range in fractured zone played an important role in determining delay time, designing a blast and understanding the mechanism of rock fragmentation by blasting [30]. Therefore, the influences of initial stress on crack length, crack velocity, and damage range were analyzed in detail in the following sections.…”
Section: Effect Of Initial Stress On Crack Propagation In Fractured Zonementioning
confidence: 99%
“…In addition, it can be found that each of the three energies varies over a large range since energy efficiency is affected by many factors such as burden, spacing, confinement, delay time, charge parameters, initiation, and the like. For example, model blasts indicated that: (1) stemming conditions affected the initiation of gas ejection out of blastholes (Zhang et al 2021); (2) unstemmed holes wasted 25% of the explosive energy (Zhang et al 2020a) available for rock fragmentation, compared with partially-stemmed blasts; (3) the specific charge influenced the crack propagation velocity (Chi et al 2019b). In addition, field measurements by Brinkmann (1990) indicated that unstemmed blastholes in underground mining blasts wasted 50% of the explosive energy in the form of 'leaking' gases, compared with fully-stemmed blastholes.…”
Section: Energy Components In Rock Blastingmentioning
confidence: 99%